Use of Nanomodified Clinoptilolite as an Additions to Building Materials - G. P. Tsintskaladze; V. G. Tsitsishvili; P. E. Tskhvitaridze; B. F. Keshelava; G. Sh. Tatarashvili; T. V. Sharashenidze (Хімія, фізика та технологія поверхні, 2010)
Natural zeolite clinoptoline from Georgian origin and its nanomodified forms have been used for modification of structures of the composite building materials. Characteristics of this zeolite have been studied by thermal analysis, IR spectroscopy, and adsorption methods. The testing results of the zeolite-containing cement have shown that introduction of zeolite (treated at high temperature) into the composition of cement improves its physical-mechanical properties and whole nanomodification of zeolite with plasticizers significantly decreases water-cement ratio improves its mechanical properties and quickens the setting time.